Influence of Work Discipline, Job Satisfaction, and Motivation Work on Employee Performance At the Deputy Field Prosperous Families and Family Building BKKBN - Ade Aisa Kusumaningtyas; Beureukat; Adam Nurkholik; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to determine and analyze the influence of work discipline, job satisfaction, and work motivation on employee performance at Deputi Bidang Keluarga Sejahtera dan Pembangunan Keluarga BKKBN. The data source for this research uses primary data in the form of a questionnaire, the research data is given to 80 employee respondents at Keluarga Sejahtera dan Pembangunan Keluarga BKKBN In taking the sample for this study using the Saturation Sampling, the data analysis technique used was multiple linear regression and hypothesis testing using t-statistics processed in SPSS 27 to test the regression coefficients. Based on the partial research results, it was found that work discipline has a positive and significant effect on employee performance, job satisfaction has a positive and significant effect on employee performance, and work motivation has a positive and significant effect on employee performance.